FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN UMKM MEMILIH PEMBIAYAAN DI BANK SYARIAH - Tatang Sutarjo; Karsono Karsono (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2024)
The decision of Micro, Small, and Medium Enterprises (MSMEs) to choose financing in Islamic banks is influenced by various factors that affect business sustainability and growth. This study aims to analyze the factors affecting MSMEs' decisions in selecting financing in Islamic banks in Ciamis Regency. The research involved 100 MSME owners selected using purposive sampling techniques based on business type, duration, and experience with Islamic financing. A quantitative approach was applied, with structured questionnaires as the data collection instrument. Data analysis was conducted using multiple regression methods to examine the influence of variables such as religiosity, understanding of Islamic principles, banking services, and profit-sharing rates on financing decisions. The results show that religiosity and understanding of Islamic principles significantly impact MSME decisions, while banking services and profit-sharing rates also play relevant roles. The study concludes that increasing public understanding of Islamic banking products and principles can enhance Islamic banks' attractiveness to MSMEs. This research provides practical implications for Islamic banks to improve their services and education efforts toward potential MSME customers.